PERAN KONSELOR MELALUI BIMBINGAN KELOMPOK DENGAN PROBLEM BASED LEARNING UNTUK PENINGKATAN KARAKTER PEDULI LINGKUNGAN SISWA - Sri Murniasih (Center for Research and Community Service (LPPM) University of Abulyatama, 2021)
The main objective of sustainable development is to meet basic human needs while maintaining the life support systems of planet earth. In everyday life, building awareness of the environment can be pursued through education. To support the commitment of the community and international government in efforts to protect the earth from pollution and damage by implementing Environmental Education, which is the key to preparing people with expertise, knowledge, values and attitudes to care for the environment so that they can actively participate in solving environmental problems. With the role of counseling teachers through group guidance services which are expected to provide understanding and knowledge of students about the character of caring for the environment. This study is to determine how the role of the counselor in improving the character of environmental care through group guidance services with a problem-based learning model.This research method used a quasi-experimental design with a pretest-post-test control group design. shows that there is a difference in the average posttest data on students' caring attitudes between the experimental class and the control class. This is evidenced by the value of tcount 7.023 <ttable 2.02 and a significant (p value) of 0.000 which is smaller than 0.05. So it can be concluded that the statistical results with the t test show that there is a significant difference between the caring attitude of the experimental class students and the control class students' caring attitude at the time of the post-test. It can be explained that the implementation of group guidance services has been carried out by the counselor very well through the implementation of all syntax indicators by the teacher with an average total implementation of 87.63% with a very good category.